Distinction of fungal polysaccharides by N/C ratio and mid infrared spectroscopy - Gomba, Gordon Karikoga; Synytsya, Andriy; Švecová, Petra; Coimbra, Manuel A; Čopíková, Jana (International journal of biological macromolecules, 2015)
A set of fungal polysaccharide samples was characterised by elemental analysis and FTIR spectroscopy and compared with reference chitins, chitosans and β-D-glucans. The nitrogen to carbon (N/C) values and FTIR spectra were used to compare the samples based on their composition. It was found that the N/C ratio correlates well with deacetylation degree (DD) of chitosans and chitin/glucan ratio R(chit) of fungal chitin – β-D-glucan complexes with the exception of some samples having significant nitrogen and/or carbon admixtures. FTIR spectroscopy was indicative for the N-acetylation of chitins (chitosans) as well as for the chitin (chitosan) contribution to fungal polysaccharide preparations. Multivariate analyses of the FTIR data (HCA, PCA) discriminated samples and reference materials into several clusters depending on their similarity. Chitosan lactates, chitosan – β-D-glucans and chitin – β-D-glucans of high and low amounts of chitin were successfully discriminated from the reference polysaccharides and from each other. The proposed procedures based on the N/C ratio and multivariate analyses of FTIR spectra may be used in screening fungal polysaccharide preparations.
Keywords: Species Specificity; dusík; Carbon; fungální polysacharidy; spektrofotometrie infračervená; Fungal Polysaccharides; uhlík; Spectrophotometry, Infrared; Nitrogen; Aspergillus niger; druhová specificita